Self-repairing microcapsule, self-repairing flocking adhesive, self-repairing flocking material and preparation method thereof
By introducing self-healing microcapsules and self-healing flocking adhesives into flocking materials, the core-shell structure of isocyanate and polyethylene adipate is solved, and the mechanical damage problem of flocking materials is realized. Repair function, extends service life and reduces maintenance costs.
Patent Information
- Application Number
- CN202411263758.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-24
AI Technical Summary
Existing flocking materials are susceptible to mechanical damage in daily use, resulting in shorter service life, reduced aesthetics and increased maintenance costs.
Using self-healing microcapsules and self-healing flocking adhesive, the core-shell structure is formed by adding isocyanate and polyethylene adipate to the adhesive, and the shell releases self-healing during damage. The agent undergoes chemical reaction repair.
It significantly improves the durability and service life of flocking materials, reduces maintenance costs, and broadens its application areas.
Smart Images

Figure CN119177093A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of flocking technology, and in particular to a self-repairing microcapsule, a self-repairing flocking adhesive, a self-repairing flocking material and a preparation method thereof. Background Art
[0002] As a process of precisely implanting fiber materials into the surface of a substrate, flocking technology has been widely used in many industries, especially in the fields of automotive interiors, high-end furniture, and fashion clothing. The flocking layer is favored by the market for its unique touch, good visual effects, and excellent sound insulation and heat insulation performance. However, with the frequent contact and friction of these products in daily use, the flocking layer will inevitably suffer various forms of mechanical damage, such as fiber shedding, surface wear, and cracks caused by long-term stress.
[0003] These damages not only seriously affect the aesthetics of flocking products, but also shorten their service life, increase consumers' replacement costs, and also pose a challenge to manufacturers' brand image and market competitiveness. Therefore, how to effectively extend the service life of the flocking layer and improve its ability to resist mechanical damage has become a key technical issue that needs to be solved in the industry. Summary of the invention
[0004] In order to improve the problem that the current flocking layer has a short service life due to mechanical damage, the present application provides a self-repairing microcapsule, a self-repairing flocking adhesive, a self-repairing flocking material and a preparation method thereof.
[0005] In the first aspect, the present application provides a self-repairing microcapsule, which adopts the following technical solution: A self-repairing microcapsule for self-repairing flocking material, comprising the following raw materials in parts by weight: 15-25 parts of shell material monomer, 50-70 parts of self-repairing agent, and 25-40 parts of emulsifier; The self-healing agent is a mixture of isocyanate and polyethylene adipate in a mass ratio of 4-5:5-6, and the shell material monomer is isocyanate.
[0006] Optionally, the emulsifier may be Span 80 or Tween 80.
[0007] Optionally, the self-repairing microcapsule comprises the following raw materials in parts by weight: 20 parts of shell material monomer, 55 parts of self-repairing agent, and 25 parts of emulsifier.
[0008] Optionally, the isocyanate includes one or more of monoisocyanate, toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and isophorone diisocyanate (IPDI).
[0009] The self-healing agent in the present application can be mixed in the water phase with an emulsifier to form an oil-in-water emulsion. At the same time, the isocyanate as the shell material monomer will also react with the hydroxyl group in the water to form a polyurethane shell. The self-healing agent is gradually coated by the shell during the shell formation process, thereby forming a core-shell structure in which the self-healing agent is encapsulated inside and the polyurethane shell is wrapped outside.
[0010] The self-healing agent is a uniform compound of isocyanate and polyethylene adipate (PES), wherein the polyethylene adipate is preferably medium molecular weight PES (molecular weight is usually between 2000-4000g / mol). When the shell structure is damaged, this mixture can undergo a chemical reaction to generate polyurethane. The reaction speed is relatively fast and usually occurs at room temperature to medium temperature (e.g., 50°C to 80°C). This reactivity is suitable for applications in rapid curing and repairing. PES has good wear resistance and flexibility. After the shell of the self-healing microcapsule is damaged, when the isocyanate and other components are cross-linked to form a polyurethane network, PES is entangled or blended in the network, which can improve the flexibility and ductility of the material, and is suitable for use in self-healing materials that require higher flexibility or low temperature resistance.
[0011] Optionally, PES can be selected from the following grades: S1045, Desmophen 631A or Millester4004.
[0012] Optionally, the self-repairing microcapsules are prepared by the following preparation method: Step S11: using the emulsifier to mix the self-repairing agent in the water phase to form a water-in-oil emulsion; Step S12: adding the shell material monomer dropwise into the water-in-oil emulsion, and performing emulsion polymerization reaction under stirring; Step S13: obtaining self-repairing microcapsules by filtering, washing and drying.
[0013] Optionally, in step S11, the emulsification temperature is 25°C, the emulsification time is 30 minutes, and the stirring speed is 1000 rpm; in step S12, the reaction temperature is 35°C, the reaction time is 2 hours, and the stirring speed is 800 rpm; in step S13, the drying temperature is 40°C, and the drying time is 12 hours.
[0014] Through the above operation, the self-healing agent can be wrapped in the polyurethane shell to form a stable microcapsule structure. The preparation method is simple and efficient, easy to industrialize, and can accurately control the size and distribution of the microcapsules, providing high-quality raw materials for the subsequent preparation of flocking adhesives.
[0015] In a second aspect, the present application provides a self-repairing flocking adhesive, which adopts the following technical solution: A self-repairing flocking adhesive comprises a uniformly mixed adhesive matrix and the self-repairing microcapsules, wherein the amount of the self-repairing microcapsules is 10%-20% of the mass of the adhesive matrix.
[0016] This adhesive not only has the basic properties of traditional flocking adhesives, but also has self-repairing functions. By evenly mixing self-repairing microcapsules into the adhesive matrix, it achieves the purpose of automatically repairing cracks and defects when the flocking material is damaged. This design significantly improves the durability and service life of the flocking material and reduces maintenance costs.
[0017] Optionally, the adhesive matrix comprises the following raw materials in parts by weight: 70-85 parts of polyurethane prepolymer, 5-15 parts of plasticizer, 3-6 parts of stabilizer, and 2-5 parts of catalyst.
[0018] Optionally, the adhesive matrix comprises the following raw materials in parts by weight: 75 parts of polyurethane prepolymer, 10 parts of plasticizer, 5 parts of stabilizer, and 3 parts of catalyst.
[0019] As the main component of the adhesive, the polyurethane prepolymer provides good bonding strength and wear resistance. Moreover, the polyurethane prepolymer in this application is generated by the reaction of polyols and diisocyanates, and has active groups such as unreacted isocyanate groups or hydroxyl end groups. When the self-repairing microcapsules are damaged and released, the active groups in the polyurethane prepolymer can cross-link with the isocyanate in the self-repairing agent to form a new polyurethane network, thereby filling the damaged area; the addition of plasticizers improves the flexibility and processing properties of the adhesive; stabilizers and catalysts respectively ensure the long-term stability and reaction rate of the adhesive. In addition, in addition to accelerating the reaction in the adhesive matrix, the catalyst can also accelerate the cross-linking reaction between the self-repairing agent and the polyurethane prepolymer in the adhesive matrix during the self-repairing process to improve the reaction efficiency of the self-repairing.
[0020] Optionally, the adhesive matrix further comprises 5-10 parts of a strengthening agent.
[0021] Optionally, the adhesive matrix also includes 7 parts of a strengthening agent.
[0022] Optionally, the reinforcing agent is CNTs, nanocellulose or PLA nanofibers.
[0023] The present application also introduces a reinforcing agent component into the adhesive matrix, which can not only enhance the mechanical properties of the self-repairing flocking adhesive, making the final material more durable, but also improve the tensile, tear and bending resistance; the nanofibers can effectively prevent the expansion of cracks when the material is subjected to stress, thereby improving the fracture toughness of the material and reducing the risk of damage to the material during use; the nanofibers can also enhance the interfacial adhesion between the adhesive layer and the flocking layer, making the flocking layer less likely to fall off under the action of external force, thereby extending the service life of the material; in addition, the nanofibers can form a stable network structure in the adhesive, prevent the sedimentation of other fillers, and improve the uniformity and stability of the material.
[0024] Optionally, the self-repairing flocking adhesive is prepared by the following preparation method: Step S21: the polyether polyol and diisocyanate are stirred evenly and then heated to 80-90° C. for 2 hours to form a polyurethane prepolymer with a hydroxyl terminal; Step S22: After cooling the polyurethane prepolymer to room temperature, adding a plasticizer, a stabilizer and a catalyst, and stirring evenly; Step S23: gradually adding the reinforcing agent to the product obtained in step S22, and stirring evenly to obtain the adhesive matrix; Step S24: while the adhesive matrix is stirred at a low speed, the self-repairing microcapsules are slowly and evenly added into the adhesive matrix to obtain the adhesive matrix.
[0025] During the process of adding the self-healing microcapsules, the adhesive matrix is kept at a low stirring speed to reduce the mechanical shear force on the self-healing microcapsules, thereby preventing the microcapsules from breaking during the stirring process; the self-healing microcapsules are gradually added to the adhesive matrix in a slow and uniform manner, and the stirring intensity can be controlled by using a disperser or a low speed gear of the agitator to ensure that the microcapsules can be evenly distributed in the adhesive matrix without being destroyed.
[0026] Optionally, in step S21, the molar ratio of the polyether polyol to the diisocyanate is preferably 1.2-1.5:1.
[0027] In common polyurethane synthesis, the molar ratio of polyether polyol to diisocyanate is usually between 1:1 and 1:2. However, in the present application, by increasing the amount of polyether polyol used in the process of forming the polyurethane prepolymer, so that it exists in excess, sufficient hydroxyl groups can be provided in the reaction system, so that the self-repairing microcapsules can react with the isocyanate in the self-repairing agent after rupture to form a new polyurethane network. At the same time, the co-existence of the polyurethane prepolymer and the polyether polyol can provide a more complex network structure, which helps to enhance the mechanical properties and self-repairing properties of the material.
[0028] Optionally, the polyether polyol includes one or more of polyoxypropylene ether polyol (PPG) with a molecular weight of 1500-2000, polytetramethylene ether polyol (PTMEG) and tetramethylene ether copolymer polyol.
[0029] Optionally, the diisocyanate includes one or more of toluene diisocyanate (TDI), diphenylmethane-4,4'-diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), paraphenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), 1,4-cyclohexane diisocyanate (CHDI) and naphthalene-1,5-diisocyanate (NDI).
[0030] Optionally, in step S22, a high-speed stirrer is used to stir the mixture at a stirring speed of 2000 rpm for 30 minutes to ensure that all substances are stirred evenly.
[0031] Optionally, in step S23, a high-speed stirrer is used to stir the mixture at a stirring speed of 2000 rpm at 25° C. for 0.5-1 hour to ensure that the reinforcing agent is evenly distributed in the adhesive matrix.
[0032] Optionally, in step S24, the stirring speed of the adhesive matrix is 200-500 rpm.
[0033] By limiting the stirring speed when adding the self-healing microcapsules, it helps to ensure the uniform dispersion and stable mixing of the self-healing microcapsules in the adhesive matrix. Too fast a stirring speed may cause the microcapsules to rupture; too slow a stirring speed may not achieve sufficient mixing. Therefore, this limited range not only ensures the mixing effect but also avoids unnecessary losses.
[0034] In a third aspect, the present application provides a method for preparing a self-repairing flocking material, using the following technical solution: A method for preparing a self-repairing flocking material comprises the following steps: Step S31: substrate pretreatment; Step S32: evenly coating the self-repairing flocking adhesive on the surface of the substrate and allowing to stand; Step S33: uniformly implanting the fiber material into the self-repairing flocking adhesive under the condition of an electric field strength of 50 kV; Step S34: subjecting the flocked product to thermal curing treatment to obtain the product.
[0035] Optionally, the specific steps of step S31 are as follows: using ethanol and deionized water to clean the surface of the substrate, and then performing a drying process, wherein the drying temperature is 60° C. and the drying time is 1 hour.
[0036] Optionally, in step S31, the substrate may be polyisoprene rubber, styrene-butadiene rubber, nitrile rubber, EPDM rubber, polyurethane, latex or silicone.
[0037] Optionally, in step S32, the coating thickness of the self-repairing flocking adhesive is 0.1-0.3 mm.
[0038] Optionally, in step S32, the coating thickness of the self-repairing flocking adhesive is 0.2 mm.
[0039] Optionally, in step S32, the coating is allowed to stand for 10 minutes after the coating is completed to ensure that the self-repairing flocking adhesive is evenly distributed.
[0040] Optionally, in step S33, the length of the fiber material is 1 mm.
[0041] Optionally, in step S33, the fiber material is made of nylon, viscose, acrylic, polyester or genuine leather.
[0042] Optionally, in step S34, the temperature of the thermal curing treatment is 80° C., and the time of the thermal curing treatment is 2 hours.
[0043] In a fourth aspect, the present application provides a self-repairing flocking material, which adopts the following technical solution: A self-repairing flocking material is prepared by adopting the above-mentioned preparation method.
[0044] Optionally, the self-repairing flocking material comprises basal layer; An adhesive layer formed on the surface of the base layer by the self-repairing flocking adhesive; The flocking layer is made of the fiber material and is bonded to the base layer through an adhesive layer.
[0045] This material not only has the advantages of traditional flocking materials, such as beautiful, wear-resistant and soft, but also has a unique self-repairing function. When cracks or damage appear on the surface of the material, the self-repairing microcapsules inside can respond quickly and release self-repairing agents to repair cracks and defects through chemical reactions, thereby restoring the integrity and performance of the material. This self-repairing function significantly improves the durability and service life of flocking materials, reduces maintenance costs and broadens its application areas.
[0046] In summary, the present application includes at least one of the following beneficial effects: 1. The present application prepares a self-healing agent into a core-shell structure in which the self-healing agent is encapsulated inside and a polyurethane shell is wrapped outside. The shell can remain intact during normal use of the material to protect the internal self-healing agent. When the flocking layer or the adhesive layer is damaged by external force (such as scratches, wear, impact, etc.), the microcapsule shell distributed in the adhesive will rupture, and the internal self-healing agent will be released into the damaged area. The released self-healing agent will fill the damaged area and solidify to form a new material after reacting with air, moisture or other components in the adhesive in the external environment. The newly formed material can effectively fill cracks or damage, thereby restoring the integrity and functionality of the material.
[0047] 2. The present application successfully prepares a flocking material with self-repairing function by introducing self-repairing microcapsules into the self-repairing flocking adhesive. When the self-repairing flocking layer is mechanically damaged, the damage can be effectively repaired by releasing and curing the self-repairing agent, thereby improving the durability and service life of the flocking layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a microscopic magnified image of the self-repairing microcapsule prepared in Example 1 of the present application; Figure 2 is an enlarged schematic diagram of the self-repairing microcapsules prepared in Example 4 of the present application being uniformly distributed in the adhesive matrix; Figure 3 is a schematic structural diagram of the self-repairing flocking material prepared in Example 9 of the present application; Figure 4 This is a diagram of the working principle of the self-healing microcapsule; Figure 5a This is the surface morphology of the material just after the scratch; Figure 5b This is the surface morphology of the material 24 hours after the scratch. DETAILED DESCRIPTION
[0049] The present application is further described below in conjunction with specific embodiments.
[0050] Example 1 Example 1 provides a self-repairing microcapsule, wherein the raw materials for preparing the microcapsule include 20g of a shell material monomer, toluene diisocyanate, 55g of a self-repairing agent, and 25g of an emulsifier, Tween 80, wherein the self-repairing agent is compounded by 25g of toluene diisocyanate and 30g of polyethylene adipate; the specific preparation method is as follows: Step S11: at 25° C., the self-healing agent is mixed in the water phase using an emulsifier Tween 80 to form an oil-in-water emulsion, the stirring speed is 1000 rpm, and the emulsification time is 30 minutes; Step S12: adding the shell material monomer dropwise into the water-in-oil emulsion at 35° C., and performing emulsion polymerization for 2 hours under stirring at a speed of 800 rpm; Step S13: obtaining self-healing microcapsules by filtering, washing and drying, wherein the drying temperature is 40° C. and the drying time is 12 hours.
[0051] Figure 1 This is a microscopic enlarged image of the self-repairing microcapsule prepared in Example 1 of the present application. Figure 1 The self-healing microcapsules have clear surface contours, and the microcapsules present a uniform spherical or quasi-spherical structure with a size distribution between 50-110 microns. The surface of the microcapsules is smooth, without obvious surface defects or cracks, which indicates that the emulsion polymerization process used effectively controls the morphology and structure of the microcapsules. In addition, the wall thickness of the microcapsules is uniform, showing good structural integrity, which helps to stably release the internal self-healing agent when the material is damaged by stress, ensuring the effectiveness of its repair function.
[0052] Example 2-3 Embodiment 2-3 is basically the same as Embodiment 1, and the only difference is that the ratio of components in the self-repairing microcapsules is different, as shown in Table 1 for details.
[0053] Table 1 (unit: g) Example 4 Example 4 provides a self-repairing flocking adhesive, the raw materials for its preparation include 75g of polyurethane prepolymer, 10g of plasticizer dioctyl phthalate (DOP), 5g of stabilizer dibutyltin dilaurate (DBTL), 3g of catalyst diisopropylamine (DIPA), 7g of strengthener, and 10g of self-repairing microcapsules prepared in Example 1; the specific preparation method is as follows: Step S21: polyoxypropylene ether triol and toluene diisocyanate are uniformly stirred at a molar ratio of 1.5:1, and then heated to 90° C. and maintained for 2 hours to form a polyurethane prepolymer with hydroxyl ends; Step S22: 75 g of the polyurethane prepolymer is taken from the product of step S21 and cooled to room temperature, and then a plasticizer, a stabilizer and a catalyst are added, and a high-speed stirrer is used to stir at a stirring speed of 2000 rpm for 30 minutes to ensure that all substances are stirred evenly; Step S23: gradually adding PLA nanofibers to the product obtained in step S22, ensuring that the product is fully stirred after each addition, and stirring at a high-speed stirrer at a stirring speed of 2000 rpm at 25° C. for 0.5 hours to ensure that the reinforcing agent is evenly distributed in the adhesive matrix, thereby obtaining; Step S24: At a temperature of 25° C., the adhesive matrix is stirred at a low speed of 300 rpm for about 15 to 30 minutes, and the self-healing microcapsules are slowly and evenly added into the adhesive matrix.
[0054] After the preparation is completed, a small amount of samples is taken to observe the distribution of the self-healing microcapsules. Figure 2 Schematic diagram of the self-repairing microcapsules prepared in Example 4 of the present application uniformly distributed in the adhesive matrix. Figure 2 , it can be seen that the self-healing microcapsules are evenly distributed in the adhesive matrix and are not broken.
[0055] Embodiment 5-6 Examples 5-6 are substantially the same as Example 4, except that the self-repairing microcapsules used in Examples 5 and 6 are from the self-repairing microcapsules prepared in Examples 2 and 3, respectively.
[0056] Example 7 Example 7 is basically the same as Example 4, except that the amount of self-repairing microcapsules used in Example 7 is 15 g.
[0057] Example 8 Example 8 is basically the same as Example 4, except that the amount of self-repairing microcapsules used in Example 8 is 20 g.
[0058] Example 9 Embodiment 9 provides a self-repairing flocking material, which is prepared by the following method: Step S31: selecting polyisoprene rubber as the substrate and performing pretreatment, specifically, using ethanol and deionized water to clean the surface of the substrate, and then performing drying treatment, wherein the drying temperature is 60° C. and the drying time is 1 hour; Step S32: using a scraper, evenly apply the self-repairing flocking adhesive prepared in Example 4 on the surface of the substrate to a thickness of 0.2 mm, and let it stand for 10 minutes; Step S33: using an electrostatic flocking device to uniformly implant a polyester fiber material with a length of 1 mm into the self-repairing flocking adhesive under the condition of an electric field strength of 50 kV; Step S34: heat-curing the flocked product at 80° C. for 2 hours.
[0059] Figure 3 Schematic diagram of the structure of the self-repairing flocking material prepared in Example 9 of the present application. Figure 3 The self-repairing flocking adhesive is located between the substrate and the fiber material, and is used to tightly bond the fiber material to the substrate. Self-repairing microcapsules are evenly distributed in the self-repairing flocking adhesive, and the size of the self-repairing microcapsules is in the range of 50-110 microns. Figure 4 This is a diagram of the working principle of self-repairing microcapsules. Figure 4 When the flocking layer or adhesive layer is damaged by external force (such as scratches, abrasion, impact, etc.), the microcapsule shell distributed in the adhesive will break, and the internal self-healing agent will be released into the damaged area. The released self-healing agent will fill and repair the damaged area.
[0060] Examples 10-13 Examples 10-13 are substantially the same as Example 9, except that the self-repairing flocking adhesives used in Examples 10-13 are from Examples 5-8, respectively.
[0061] Comparative Example 1 Comparative Example 1 is substantially the same as Example 9, except that the flocking adhesive used in Comparative Example 1 is different from the flocking adhesive used in Example 9. The flocking adhesive in Comparative Example 1 does not contain self-repairing microcapsules, and its preparation raw materials include 75g of polyurethane prepolymer, 10g of plasticizer dioctyl phthalate (DOP), 5g of stabilizer dibutyltin dilaurate (DBTL), 3g of catalyst diisopropylamine (DIPA), and 7g of strengthener; the specific preparation method is as follows: Step S21: polyoxypropylene ether triol and toluene diisocyanate are uniformly stirred at a molar ratio of 1.5:1, and then heated to 90° C. and maintained for 2 hours to form a polyurethane prepolymer with hydroxyl ends; Step S22: 75 g of the polyurethane prepolymer is taken from the product of step S21 and cooled to room temperature, and then a plasticizer, a stabilizer and a catalyst are added, and a high-speed stirrer is used to stir at a stirring speed of 2000 rpm for 30 minutes to ensure that all substances are stirred evenly; Step S23: gradually add PLA nanofibers to the product obtained in step S22, ensuring that it is fully stirred after each addition, and stir at a high-speed stirrer at a stirring speed of 2000 rpm at 25° C. for 0.5 hours to ensure that the reinforcing agent is evenly distributed in the adhesive matrix, thereby obtaining a flocking adhesive.
[0062] Performance Testing 1. Scratch test: The self-repairing flocking material prepared in Example 9 was subjected to a scratch test to evaluate its mechanical damage repair performance. A scratch with a depth of 0.1 mm was made on the surface of the flocking layer of the sample using a scratch tester to observe the self-repair effect of the damaged area. After the scratch, the sample was left for 24 hours, and the surface morphology of the flocking layer before and after the damage was observed under a microscope.
[0063] Figure 5a This is the surface morphology of the material just after the scratch; Figure 5b This is the surface morphology of the material 24 hours after the scratch. Figure 5aand Figure 5b It can be seen that 24 hours after the scratches were made, the scratches on the surface of the material have basically disappeared after being repaired by the self-healing microcapsules.
[0064] 2. Abrasion test: The self-repairing flocking materials prepared in Examples 9-13 and Comparative Example 1 were subjected to wear tests to evaluate their wear resistance. According to the American standard ASTM D 3884-2009, 5 samples were taken from each of the self-repairing flocking materials prepared in Examples 9-13 and Comparative Example 1, with a sample size of 150 mm × 150 mm, a load of 500 g, a grinding wheel model of CS-10, and abrasion for 1000 times. The surface roughness and average weight change of the samples before and after abrasion were recorded. The specific results are shown in Table 2.
[0065] Table 2 Abrasion test results It is not difficult to see from the results in Table 2 that after the self-repairing flocking materials of Examples 9-13 are mechanically damaged, the self-repairing microcapsules are ruptured to release the self-repairing agent, thereby significantly reducing the surface roughness of the damaged area.
[0066] In the abrasion test, the sample will lose part of its mass due to material wear after friction. This mass reduction (i.e. weight change) directly reflects the wear resistance of the material. The smaller the weight change, the less mass the material loses during the wear process, indicating that the material has better wear resistance. It can also be seen from Table 2 that the wear resistance of the materials in Examples 9-13 is significantly better than that in Comparative Example 1. The reason for this result is mainly that the self-repairing flocking adhesive of the present application evenly contains a number of self-repairing microcapsules. When the material is damaged during the wear process, the microcapsules rupture and release self-repairing agents, which quickly fill and repair the damaged area. This real-time repair mechanism effectively reduces the loss of the material during the friction process, so the weight change after wear is small.
[0067] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A self-repairing microcapsule for self-repairing flocking material, characterized in that: The raw materials include the following parts by weight: 15-25 parts of shell material monomer, 50-70 parts of self-healing agent, and 25-40 parts of emulsifier; The self-healing agent is a mixture of isocyanate and polyethylene adipate in a mass ratio of 4-5:5-6, and the shell material monomer is isocyanate.
2. The self-repairing microcapsule for self-repairing flocking material according to claim 1, characterized in that: It is prepared by the following preparation method: Step S11: using the emulsifier to mix the self-repairing agent in the water phase to form a water-in-oil emulsion; Step S12: adding the shell material monomer dropwise into the water-in-oil emulsion, and performing emulsion polymerization reaction under stirring; Step S13: obtaining self-repairing microcapsules by filtering, washing and drying.
3. A self-repairing flocking adhesive, characterized in that: The invention comprises a uniformly mixed adhesive matrix and the self-repairing microcapsules according to claim 2, wherein the amount of the self-repairing microcapsules is 10%-20% of the mass of the adhesive matrix.
4. The self-repairing flocking adhesive according to claim 3, characterized in that: The adhesive matrix comprises the following raw materials in parts by weight: 70-85 parts of polyurethane prepolymer, 5-15 parts of plasticizer, 3-6 parts of stabilizer and 2-5 parts of catalyst.
5. The self-repairing flocking adhesive according to claim 4, characterized in that: The adhesive matrix also includes 5-10 parts of a strengthening agent.
6. The self-repairing flocking adhesive according to claim 5, characterized in that: The reinforcing agent is CNTs, nanocellulose or PLA nanofiber.
7. The self-repairing flocking adhesive according to claim 5, characterized in that: The self-repairing flocking adhesive is prepared by the following preparation method: Step S21: the polyether polyol and diisocyanate are stirred evenly and then heated to 80-90° C. and maintained for 2 hours to form a polyurethane prepolymer with a hydroxyl terminal; Step S22: After cooling the polyurethane prepolymer to room temperature, adding a plasticizer, a stabilizer and a catalyst, and stirring evenly; Step S23: gradually adding the reinforcing agent to the product obtained in step S22, and stirring evenly to obtain the adhesive matrix; Step S24: while the adhesive matrix is stirred at a low speed, the self-repairing microcapsules are slowly and evenly added into the adhesive matrix to obtain the adhesive matrix.
8. The self-repairing flocking adhesive according to claim 7, characterized in that: In the step S24, the stirring speed of the adhesive matrix is 200-500 rpm.
9. A method for preparing a self-repairing flocking material, characterized in that: The steps include: Step S31: substrate pretreatment; Step S32: uniformly coating the self-repairing flocking adhesive according to any one of claims 3 to 8 on the surface of the substrate and allowing to stand; Step S33: uniformly implanting the fiber material into the self-repairing flocking adhesive under the condition of an electric field strength of 50 kV; Step S34: subjecting the flocked product to thermal curing treatment to obtain the product.
10. A self-repairing flocking material, characterized in that: The preparation method according to claim 9 is used for preparation.
